ANALISIS PENGARUH PELATIHAN DAN KOMPENSASI TERHADAP KINERJA PERAWAT DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (Survei pada Perawat RSUD Dr. Harjono S. Kabupaten Ponorogo) - Puspitasari, Deny; Suddin, Alwi; Sutarno, Sutarno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This study entitled "Analysis of the Effect of Training and Compensation on Nurse's Performance with Job Satisfaction as a Mediation Variable (Survey on nurses at Dr. Harjono S Hospital, Ponorogo Regency)". The purpose of the study was to analyze the significance of the effect of training and compensation on the performance of nurses with job satisfaction as a mediating variable in nurses at the RSUD Dr. Harjono S Ponorogo Regency. The benefits of practical research can be taken into consideration in making management decisions to improve the quality of service in the future and academically can increase knowledge, especially regarding the development of human resource management. The sample in this study amounted to 100 respondents from a population of 375 nurses with the calculation of the number of respondents using the Simple Random Sampling technique. The results of this study found that Training and Compensation had an effect (P < 0.05) on Job Performance and Satisfaction. Job Satisfaction has an effect (P < 0.05) on employee performance.